Selected works of Mao Tse-tung. - Mao, Zedong, 1893-1976 (Foreign Languages Press, 1965)
Selected Works of Mao Tse-Tung, Volume I focuses on the thoughts of Mao Tse-Tung on differences in social structure, communism, revolution, economics, war tactics, and welfare of the masses.